Applications of NMR spectroscopy. Volume 1 - Rahman, Atta-ur-, 1942-; Choudhary, M. Iqbal (Shiqah, United Arab Emirates : Bentham Science Publishers Ltd., 2015)
Applications of NMR Spectroscopy is an eBook series devoted to publishing the latest advances in the application of nuclear magnetic resonance (NMR) spectroscopy in practical situations.
Cover; Title Page; EUL; Contents; Preface; List of Contributor; Section A; Chapter 01; Chapter 02; Section B; Chapter 03; Chapter 04; Section C; Chapter 05; Chapter 06; Index; Back Cover
Includes bibliographical references at the end of each chapters and index.
Print version record.
Elsevier
Keywords: Nuclear magnetic resonance spectroscopy; SCIENCE / Chemistry / Analytic; Nuclear magnetic resonance spectroscopy; Electronic books; Electronic books